Mushrooms, Microdosing, and Mental Illness: The Effect of Psilocybin on Neurotransmitters, Neuroinflammation, and Neuroplasticity - Kinderlehrer DA (Neuropsychiatric Disease and Treatment)
Daniel A Kinderlehrer Private Practice, Denver, CO, USACorrespondence: Daniel A Kinderlehrer, Email kinderlehrer@gmail.comAbstract: The incidence of mental health disorders is increasing worldwide. While there are multiple factors contributing to this problem, neuroinflammation underlies a significant subset of psychiatric conditions, particularly major depressive and anxiety disorders. Anti-inflammatory interventions have demonstrated benefit in these conditions. Psilocin, the active ingredient of mushrooms in the Psilocybe genus, is both a potent serotonin agonist and anti-inflammatory agent, increases neuroplasticity, and decreases overactivity in the default mode network. Studies using hallucinogenic doses of psilocin under the supervision of a therapist/guide have consistently demonstrated benefits to individuals with depression and end-of-life anxiety. Microdosing psilocybin in sub-hallucinogenic doses has also demonstrated benefit in mood disorders, and may offer a safe, less expensive, and more available alternative to full doses of psilocybin for mood disorders, as well as for other medical conditions in which inflammation is the principal pathophysiology.Keywords: Psilocybin, psilocin, microdose, depression, anxiety, neuroinflammation, anti-inflammatory